Dampak Suhu Pengeringan terhadap Karakteristik Tepung Labu Kuning (Cucurbita Moschata Durch) yang dihasilkan - Amalia, Sinta (Ma'soem University, 2024)
Yellow pumpkin (Cucurbita moschata D) is a type of fruit with a huge volume and high water content, its shelf life is short. therefore it needs to be processed into a product that is more durable and practical, for example into flour. Pumpkin flour is processed by drying it and then grinding it so that flour can be produced with a typical yellow pumpkin color, through pre-treatment by blanching. The goal of this study is to determine the ideal drying temperature for producing pumpkin flour with the finest qualities. The research method used was an experimental method with a Randomized Group Design (RAK). The drying temperature treatment consisted of 50°C, 60°C, 70°C, 80°C, 90°C, each repeated 5 times. Analysis of the characteristics of flour in this study included water content, beta-carotene content, yield and organoleptic tests on color, taste, aroma and texture. The research results showed that a drying temperature of 70°C produced the best characteristics of pumpkin flour. This determination was based on a water content of 14.20%, yield of 21.8%, and beta-carotene of 221.00 ppm. Meanwhile, a drying temperature of 50°C produces the preferred color, taste and aroma of pumpkin flour.